1986
DOI: 10.1029/jc091ic01p00896
|View full text |Cite
|
Sign up to set email alerts
|

Geochemistry and deposition of 7Be in river‐estuarine and coastal waters

Abstract: The atmospheric flux of cosmogenic ?Be (53.3-day half-life) and the mode of ?Be deposition in riverestuarine and coastal environments have been examined. The atmospheric flux of ?Be commonly supports inventories ranging from 1.0 to 2.0 pCi/cm 2 (1 pCi = 0.037 Bq). Beryllium 7 concentrations in water phase samples, collected across salinity gradients in several estuaries along the eastern coastline of the United States, range from 0.03 to 0.53 pCi/L and primarily reflect variations in ?Be supply and sorption ki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

9
97
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 181 publications
(106 citation statements)
references
References 29 publications
9
97
0
Order By: Relevance
“…We demonstrate that these zones, even in low-order streams, may sequester significant quantities of fine particulate material, contaminants, and nutrients (33). The continuous processes of fluvial redistribution in small catchments are, in turn, important in supplying organic material (34,35,36) and soil carbon (37,38) to larger river systems, lakes, wetlands, and estuaries (39,40). By extrapolation the same may be expected of iodine (41,42,4).…”
Section: Resultsmentioning
confidence: 76%
“…We demonstrate that these zones, even in low-order streams, may sequester significant quantities of fine particulate material, contaminants, and nutrients (33). The continuous processes of fluvial redistribution in small catchments are, in turn, important in supplying organic material (34,35,36) and soil carbon (37,38) to larger river systems, lakes, wetlands, and estuaries (39,40). By extrapolation the same may be expected of iodine (41,42,4).…”
Section: Resultsmentioning
confidence: 76%
“…Dissolved residence times were compared to (Benoit and Hemond 1987;Balistrieri et al 1995), whereas the values of t d Be were much shorter than those previously reported for freshwater systems: 36-1100 d (Dominik et al 1989;Schuler et al 1991;Steinmann et al 1999). Although the particle reactivity of Pb is higher than that of Be in freshwater systems (e.g., Olsen et al 1986;Benoit 1995 210 Pb from the resuspension of bottom sediments. Generally, short 7 Be and 210 Pb residence times in most freshwater systems can be attributed to shallow depths and high SPM concentrations due to frequent sediment resuspension.…”
Section: Resultsmentioning
confidence: 99%
“…Like 210 Pb and 137 Cs,7 Be is mainly associated with the fine particles rather than the sand fraction. Moreover, Olsen et al (1986) observed that fine-particle deposition is the most important factor affecting the accumulation pattern and vertical distribution of 7 Be in estuarine systems.…”
Section: Long-term Sediment Accumulation Ratesmentioning
confidence: 99%